Pengaruh Harga, Relationship Marketing dan Suasana Kafe terhadap Customer Loyalty pada Café Kopi Legend Bandar Lampung - Gusnawan, Akasa; Astuti, Sri Yuli; Rahmahwaty (STIES ALIFA, 2024)
This study aims to determine the effect of price, relationship marketing and café atmosphere on customer loyalty at Legend Bandar Lampung coffee café. Customer Loyalty will provide great benefits for a business. Customer Loyalty is shown by customers who make purchases repeatedly. This research is a quantitative research with research conducted for one full month at Coffee Legend café and obtained 98 samples that have been calculated with solvin techniques. Analysis technique using multiple linear regression tests with the help of SPSS Version 22. The results of the study stated that price has a negative and significant influence on Customer Loyalty, relationship marketing has a positive but not significant influence on Customer Loyalty and the last is the café atmosphere has a positive and significant influence on Customer Loyalty